A case report of an unusual presentation of ocular rhinosporidiosis as a conjunctival cystic mass. (2nd January 2017) - Shah, Sangeeta; Lavaju, Poonam; Bharati, Priyanka; Joshi, Icchya
ABSTRACT: Ocular involvement of rhinosporidiosis is seen in about 15% of cases and clinically appears as a freely mobile, granular, pink, fleshy sessile or pedunculated mass. The conjunctiva is the most common site of origin. A 25-year-old male presented with a painless mass in the lower part of the left eye for 6 months which was gradually progressive. Examination revealed a pedunculated mass of 15 mm x 15 mm arising from the lower palpebrae of the left eye retracting the lower lid. It appeared to be vascular with few white spots at the apex. Rest of the ocular examinations was within the normal limit. The presentations of ocular rhinosporidiosis vary. Though the conjunctival origin is very common, it may not have a classic pink fleshy appearance at all times. A vascular/cystic painless conjunctival mass should also be considered as a case of rhinosporidiosis in prone areas.